A sociolinguistic history of Scotland - Millar, Robert McColl, 1966- (Edinburgh University Press Ltd, 2020)
Robert McColl Millar examines how language has been used in Scotland since the earliest times. While primarily focusing on the histories of the speakers of Scots and Gaelic, and their competition with the encroaching use of (Scottish) Standard English, he also traces the decline and eventual 'death' of Pictish, British and Norn.